2023
DOI: 10.2174/1573405619666230213122733
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association between L1 Trabecular Attenuation from Chest Computed Tomography (CT) and Bone Mineral Density from Dualenergy X-ray Absorptiometry (DXA)

Abstract: Background: Many studies have shown that vertebral trabecular attenuation measured on CT scan corresponds well to DXA results for bone mineral density. These studies were based on crosssectional data. Hence, there were limitations in explaining the constantly changing vertebral trabecular attenuation from CT and T-score from DXA over time. Objective: This study aimed to determine the longitudinal association between the vertebral trabecular attenuation measured on computed tomography (CT) and the T-score mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Our results were consistent with that of the former study ( 12 ). Previous studies have revealed a positive correlation between HU values obtained with different CT protocols and BMD form DXA ( 12 , 15 , 22 , 23 ). Park et al ( 12 ) showed that HU values from each protocol (abdomen/pelvis contrast-enhanced CT, lumbar spine CT, and chest LDCT) were correlated (r=0.676–0.735, P<0.005) with DXA BMD.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our results were consistent with that of the former study ( 12 ). Previous studies have revealed a positive correlation between HU values obtained with different CT protocols and BMD form DXA ( 12 , 15 , 22 , 23 ). Park et al ( 12 ) showed that HU values from each protocol (abdomen/pelvis contrast-enhanced CT, lumbar spine CT, and chest LDCT) were correlated (r=0.676–0.735, P<0.005) with DXA BMD.…”
Section: Discussionmentioning
confidence: 90%
“…Chest LDCT had the highest diagnostic performance (AUC =0.701) for diagnosing osteoporosis ( 12 ). The association of L1 trabecular attenuation values and T-score appeared to be changed over time and the degree of correlation tended to decrease slightly over time, which was because osteophyte formation and degenerative scoliosis caused errors in DXA results with age ( 15 ). L1 and L2 are the current frequently-used vertebrae for QCT diagnosis ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations